BIOMASS CORROSIVENESS PREDICTION BY CHEMICAL FRACTIONATION - MªLuisa Contreras; Alberto Bahillo; Manuel Benito (Proceedings on Engineering Sciences, 2025)
The use of biomass as fuel is growing rapidly due to its advantages of CO2 neutrality and renewability. However, low-quality fuels can include considerable concentrations of ash-forming elements that negatively affect boiler operation. This study makes use of the chemical fractionation method as a useful tool to anticipate the behavior of new biomass fuels during combustion, providing valuable information on the association of ash-forming matter and the state of the elements before and after combustion. Significant differences were found for Na, Ca, Mg, S and P mode of occurrence in the diverse biomasses. Na, in both eucalyptus and industrial wood waste, was present as salts in the fluids of the plant, leading to the release of harmful Na-Chlorides. K was determined in soluble form in all cases, which involves high risk of deposits on heat transfer surfaces. Ca was bounded in soluble compounds just in wheat straw, which would induce low-temperature corrosion in the cold-end of boilers. P was recovered in the aqueous fraction only in eucalyptus wood, which may lead to bed sintering or deposits formation. Results indicate that the use of eucalyptus wood as fuel in boilers imply a major risk of generating fouling and corrosion problems.